Plasma Proenkephalin and Poor Long-Term Outcome in Renal Transplant Recipients. Issue 8 (August 2017) - Kieneker, Lyanne M.; Hartmann, Oliver; Struck, Joachim; Bergmann, Andreas; Gansevoort, Ron T.; Joosten, Michel M.; van den Berg, Else; de Boer, Rudolf A.; Bakker, Stephan J.L.
Abstract : Background: Proenkephalin (pro-ENK), a stable and reliable surrogate marker for unstable enkephalins, was found to be associated with acute kidney injury and chronic renal failure in previous studies. We aimed to investigate whether pro-ENK is linked to chronic kidney injury and poor long-term outcome in renal transplant recipients (RTR). Methods: We included 664 stable RTR and 95 healthy kidney donors. Pro-ENK was measured in plasma with a double monoclonal sandwich immunoassay. Graft failure was defined as return to dialysis therapy or retransplantation. Results: Median pro-ENK was 110 pmol/L (interquartile range [IQR], 85-148 pmol/L) in RTR and 48 pmol/L (IQR, 42-55 pmol/L) in kidney donors. Pro-ENK was correlated with estimated glomerular filtration rate (GFR) ( r s = −0.80, P < 0.001) in RTR and with measured GFR ( r s = −0.74, P < 0.001) in kidney donors. During a median follow-up of 3.1 years (IQR, 2.7-3.9 years), 45 RTR developed graft failure and 76 died. Pro-ENK was positively associated with risk (hazard ratio [HR] per standard deviation increment of the logarithm of pro-ENK; 95% confidence interval [CI]) of graft failure (HR, 4.80; 95% CI, 3.55-6.48) and mortality (HR, 1.50; 95% CI, 1.22-1.85). After adjustment of age, sex, and estimated GFR, the association of pro-ENK with graft failure remained significant (HR, 2.36; 95% CI, 1.37-4.06), whereas no significant association of pro-ENK with risk of all-cause mortality was observed (HR, 1.34; 95% CI, 0.90-2.09). Conclusions: Plasma pro-ENK is associated with kidney function as reflected by correlations with measured GFR in both RTR and kidney donors. In addition, pro-ENK was independently associated with increased risk of graft failure in RTR. Pro-ENK may aid in identification of RTR at risk for late graft failure. Abstract : Supplemental digital content is available in the text.